Asylum procedure in EU law - Raičević Nebojša (Zbornik Radova Pravnog Fakulteta u Nišu, 2016)
Directive 2013/32/EU established the common standards which the EU Member States are obliged to incorporate into their national legislations in order to regulate the procedure for deciding on asylum applications. Asylum proceedings are to be carried out by national authorities but states are obliged to comply with the standards set out in this Directive. The asylum procedure is initiated upon the request of an interested party and its aim is to examine whether a third-country national or a stateless person has met the requirements for obtaining a refugee status. Before examining the justifiability of the asylum application, it is essential to determine which EU Member State is responsible for examining the application, which is established by applying the Dublin rules. If it is established that the state of the applicant's current location is not the state responsible for examining the asylum application, the applicant will be transferred to the respective state. Then, the responsible state is obliged to institute the first instance procedure and examine the submitted application within the prescribed time limits. The examination is carried out in a regular court proceeding, unless there are reasons for instituting a special proceeding (a priority procedure, an admissibility procedure, an accelerated procedure, and a border procedure). Under this Directive, the applicant is guaranteed the right to remain in the territory of the deciding EU Member State, as long as the final decision at first instance is pending, and some other procedural guarantees aimed at ensuring that the decision on asylum has been rendered by observing the rules of fair proceedings. On the other hand, the applicant has certain obligations, the most important of which are the obligations to appear before the competent state authority, to submit the available documents, to agree to being photographed and fingerprinted, etc. If dissatisfied with the first instance decision, applicants may challenge the decision by filing an appeal with the competent national court. During the appeal proceedings, they have the right to remain in the territory of the EU Member States, except in cases involving a number of explicitly prescribed situations. If the asylum application is accepted by the final decision of the competent authority, the person acquires the legal status of a refugee and all the rights arising from that status. If the asylum application is denied, the person is obliged to leave the territory of that EU Member State.